2010
DOI: 10.1016/j.jinteco.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Competition for firms in an oligopolistic industry: The impact of economic integration

Abstract: The Strathprints institutional repository (https://strathprints.strath.ac.uk) is a digital archive of University of Strathclyde research outputs. It has been developed to disseminate open access research outputs, expose data about those outputs, and enable the management and persistent access to Strathclyde's intellectual output. Competition for Firms in an Oligopolistic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 20 publications
(22 reference statements)
8
92
2
Order By: Relevance
“…These findings give support to our theoretical predictions -big cities might actually rely less on corporate taxation -which are in contrast to research which has shown that smaller countries and countries on the periphery have lower corporate tax rates than large countries or regions in the core (Baldwin and Krugman, 2004;Haufler et al, 2009;Haufler and Wooton, 2010). This discrepancy to earlier literature can be explained with some special characteristics of local tax competition.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…These findings give support to our theoretical predictions -big cities might actually rely less on corporate taxation -which are in contrast to research which has shown that smaller countries and countries on the periphery have lower corporate tax rates than large countries or regions in the core (Baldwin and Krugman, 2004;Haufler et al, 2009;Haufler and Wooton, 2010). This discrepancy to earlier literature can be explained with some special characteristics of local tax competition.…”
supporting
confidence: 85%
“…As empirically hinterlands are typically much smaller than urban centres, our model contrasts to research which has shown that smaller countries and countries on the periphery have lower corporate tax rates than large countries or regions in the core (Baldwin and Krugman, 2004;Haufler et al, 2009;Haufler and Wooton, 2010). We then show, however, that several of our predictions coming from the sequential model are in line with stylised facts about local business tax rates in the German state of Baden-Württemberg, the same state on which our survey draws.…”
Section: Introductioncontrasting
confidence: 66%
“…In the following, we construct a simple theoretical model based on Haufler and Wooton (2009) to receive guidance for the specification of our empirical framework. We consider two jurisdictions i ∈ {a, b}, each inhabited by l i workers.…”
Section: A Simple Theoretical Modelmentioning
confidence: 99%
“…10 As in Haufler and Wooton(2009) we assume that the cost of transporting x are positive but sufficiently low to ensure that x ji > 0 and x ij > 0.…”
Section: Producersmentioning
confidence: 99%
See 1 more Smart Citation